A database design for community health data. - Hettinger BJ; Brazile RP (Computers in Nursing)
The ability to collect, store, and retrieve community health data is critical to providing health services in a timely and efficient manner. With the widespread availability of computer hardware and software that can assist in this process, the task is becoming easier. One important tool is the database management system (DBMS). A DBMS provides a conceptual framework to assist in organizing data and software that can physically store, maintain and retrieve data. The most popular DBMSs available today support the Relational Data Model, which has a conceptual framework that provides for the organization of data in tables. The authors present a database design, using the Relational Data Model, for a database of community health data.